Those Who Belong: Identity, Family Blood, and Citizenship among the White Earth Anishinaabeg (2015-10-19) - Doerfler, Jill; University of Minnesota Duluth. Department of American Indian Studies; University of Minnesota Duluth. Office of Intercultural Initiatives (2015)
Faculty Showcase Series: At Home in the World - UMD & Beyond presents Those Who Belong. Join Dr. Jill Doerfler and the American Indian Studies Department in celebrating the release of Those Who Belong. Reading, question and answer, and book signing. Department of American Indian Studies, The Office of Intercultural Initiatives